Pathological characteristics of axons and alterations of proteomic and lipidomic profiles in midbrain dopaminergic neurodegeneration induced by WDR45-deficiency - Panpan Wang; Yaping Shao; Murad Al-Nusaif; Jun Zhang; Huijia Yang; Yuting Yang; Kunhyok Kim; Song Li; Cong Liu; Huaibin Cai; Weidong Le (Molecular Neurodegeneration, 2024)
Abstract Background Although WD repeat domain 45 (WDR45) mutations have been linked to $$\upbeta$$ β -propeller protein-associated neurodegeneration (BPAN), the precise molecular and cellular mechanisms behind this disease remain elusive. This study aims to shed light on the impacts of WDR45-deficiency on neurodegeneration, specifically axonal degeneration, within the midbrain dopaminergic (DAergic) system. We hope to better understand the disease process by examining pathological and molecular alterations, especially within the DAergic system. Methods To investigate the impacts of WDR45 dysfunction on mouse behaviors and DAergic neurons, we developed a mouse model in which WDR45 was conditionally knocked out in the midbrain DAergic neurons (WDR45 cKO ). Through a longitudinal study, we assessed alterations in the mouse behaviors using open field, rotarod, Y-maze, and 3-chamber social approach tests. We utilized a combination of immunofluorescence staining and transmission electron microscopy to examine the pathological changes in DAergic neuron soma and axons. Additionally, we performed proteomic and lipidomic analyses of the striatum from young and aged mice to identify the molecules and processes potentially involved in the striatal pathology during aging. Further more, primary midbrain neuronal culture was employed to explore the molecular mechanisms leading to axonal degeneration. Results Our study of WDR45 cKO mice revealed a range of deficits, including impaired motor function, emotional instability, and memory loss, coinciding with the profound reduction of midbrain DAergic neurons. The neuronal loss, we observed massive axonal enlargements in the dorsal and ventral striatum. These enlargements were characterized by the accumulation of extensively fragmented tubular endoplasmic reticulum (ER), a hallmark of axonal degeneration. Proteomic analysis of the striatum showed that the differentially expressed proteins were enriched in metabolic processes. The carbohydrate metabolic and protein catabolic processes appeared earlier, and amino acid, lipid, and tricarboxylic acid metabolisms were increased during aging. Of note, we observed a tremendous increase in the expression of lysophosphatidylcholine acyltransferase 1 (Lpcat1) that regulates phospholipid metabolism, specifically in the conversion of lysophosphatidylcholine (LPC) to phosphatidylcholine (PC) in the presence of acyl-CoA. The lipidomic results consistently suggested that differential lipids were concentrated on PC and LPC. Axonal degeneration was effectively ameliorated by interfering Lpcat1 expression in primary cultured WDR45-deficient DAergic neurons, proving that Lpcat1 and its regulated lipid metabolism, especially PC and LPC metabolism, participate in controlling the axonal degeneration induced by WDR45 deficits. Conclusions In this study, we uncovered the molecular mechanisms underlying the contribution of WDR45 deficiency to axonal degeneration, which involves complex relationships between phospholipid metabolism, autophagy, and tubular ER. These findings greatly advance our understanding of the fundamental molecular mechanisms driving axonal degeneration and may provide a foundation for developing novel mechanistically based therapeutic interventions for BPAN and other neurodegenerative diseases.